2012
DOI: 10.1016/j.iatssr.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the self-assessed and examiner-assessed driving skills of Japanese driving school students

Abstract: a b s t r a c tPrevious research about subjective driving skills has revealed that drivers, especially younger males, tend to rate their driving skills more highly than those of the average driver. This study examines the accuracy of Japanese novice drivers' self-evaluation of their driving skills by comparing their self-assessments with assessments made by a driving examiner. We also examined the effects of gender and age on the accuracy of driver selfevaluation of their skills. A sample of Japanese driving t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
1
Order By: Relevance
“…Several studies have suggested that males tend to evaluate their own driving skills better than females (Boccara et al, 2010;Delhomme, 1991;McKenna et al, 1991). However, this result runs counter to studies that claim that the difference between sexes is not statistically significant (Boccara et al, 2011;Nakai & Usui, 2012;Sundström, 2011). Therefore, the present research suggests that males tend to self-evaluate in a more optimistic way than female subjects.…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…Several studies have suggested that males tend to evaluate their own driving skills better than females (Boccara et al, 2010;Delhomme, 1991;McKenna et al, 1991). However, this result runs counter to studies that claim that the difference between sexes is not statistically significant (Boccara et al, 2011;Nakai & Usui, 2012;Sundström, 2011). Therefore, the present research suggests that males tend to self-evaluate in a more optimistic way than female subjects.…”
Section: Resultscontrasting
confidence: 93%
“…Difference between the responses of both sexes was found, concluding that males tend to evaluate their driving skills more optimistically than females (Boccara, Delhomme, Vidal-Gomel, Dommès, & Rogalski, 2010;Delhomme, 1991;McKenna et al, 1991). Other studies indicate that despite this fact, the differences between sexes are not statistically significant (Boccara et al, 2011;Nakai & Usui, 2012) or there are no significant differences at all (Sundström, 2011). Contrary to all these results, the research by Mynttinen et al (2009) demonstrated that women overestimate abilities of "vehicle maneuver" and "economic driving" in relation to men.…”
Section: Study About the Self-assessment Of The Ability To Drivementioning
confidence: 94%
See 1 more Smart Citation
“…Next is to group the written assignments into three categories, namely: overrated, accurately rated and underrated. These terms were used extensively across various studies on self-assessment (Boud & Falchiko 1989;Gentle 1994;Suzuki 2009;Nakai & Usui 2012;Hoskins et al 2012). Accurately rated refers to assignments which are awarded the same exact marks by the first and second assessors, or the one within two points from one another.…”
Section: The Assessment Proceduresmentioning
confidence: 99%
“…On the other hand, studies concerning this theoretical framework have mainly focused on private car drivers’ risk-taking behaviours [ 27 ]. Given that prosocial and aggressive driving behaviours are more universal than risk-taking behaviours, it is of great importance to concurrently examine bus drivers’ safe and unsafe driving behaviours and deeply investigate their associations with personality and risk perceptions.…”
Section: Introductionmentioning
confidence: 99%